Legal solutions of lake monitoring systems in Poland in compliance with the Water Framework Directive - Zębek, Elżbieta Małgorzata (Review of European and Comparative Law, 2022)
The Water Framework Directive 2000/60/EC is considered a very modern strategy of water management in the EU. The purpose is to establish a framework for the protection of inland surface waters by preventing further deterioration and protecting the condition of aquatic ecosystems, as well as increasing the protection and improvement of the condition of the aquatic environment by limiting emissions and losses of priority substances. It was considered that changes in the water law in Poland during the process of implementing the guidelines of the Water Framework Directive may have contributed to widening and strengthening the monitoring system of lakes and changes in their quality, especially their ecological state. This article aims to determine the changes in legal regulations in the field of water quality/ecologically state of lakes in Poland as a result of the implementation of the WFD. The EC reports indicate that some requirements are too rigorous and complicated for Member States to implement. Water monitoring was significantly expanded and modernised which lead to improvement of lake water quality in Poland. The five-grade ecological status of lake waters and standardised biological indicators were introduced. It was highlighted that the improvement of the WFD implementation process allowed for more effective water management and the development of effective strategies for the protection of lakes in Poland and other EU countries.